A retrospective analysis of ovarian response to gonadotropins after laparoscopic unilateral or bilateral salpingectomy for hydrosalpinges. Issue 3 (17th September 2020) - Mizusawa, Yuri; Matsumoto, Yukiko; Kokeguchi, Shoji; Shiotani, Masahide
Abstract: Background and Aims: We compared the effects of unilateral and bilateral salpingectomy for hydrosalpinx on ovarian function, oocyte retrieval, and embryogenesis. Methods: We retrospectively examined the hospital records of 109 women with unilateral hydrosalpinx and 57 women with bilateral hydrosalpinges who had undergone in vitro fertilization (IVF) treatment (280 oocyte retrieval cycles) between January 2011 and December 2018. We compared age at oocyte retrieval, level of anti‐Müllerian hormone (AMH) measured within 1 year of oocyte retrieval, duration of infertility, number of previous IVF treatments, level of follicle stimulating hormone, total gonadotropin dose, number of oocytes retrieved, fertilization rate, blastocyst formation rate, and peak serum estrogen concentration. This study was approved by the institutional review board. Results: Of the women with unilateral hydrosalpinx, no significant differences were observed in ovarian response, rate of fertilization or rate of blastocyst production between the 21 women (24 cycles) who had undergone unilateral salpingectomy and the 88 women (146 cycles) who had not. Of the women with bilateral hydrosalpinges, the 13 (24 cycles) who had undergone bilateral salpingectomy had slightly lower AMH levels and significantly fewer oocytes retrieved (5.5 ± 3.9 vs 8.3 ± 5.5; P = .0068) than the 44 women (86 cycles) who had not had a salpingectomy. Women who had undergone bilateral salpingectomy also had significantly lower peak serum estrogen concentrations than those who had not undergone salpingectomy (1876.1 ± 765.9 vs 2489.5 ± 1551.4; P = .009). Conclusion: In women with hydrosalpinx, bilateral salpingectomy may reduce ovarian function and response to gonadotropins, especially the number of oocytes retrieved. Unilateral salpingectomy does not have these effects.